COPD underdiagnosis and misdiagnosis in a high-risk primary care population in four Latin American countries. A key to enhance disease diagnosis : The PUMA study (2016)
Background Acknowledgement of COPD underdiagnosis and misdiagnosis in primary care can contribute to improved disease diagnosis. PUMA is an international primary care study in Argentina, Colombia, Venezuela and Uruguay. Objectives To assess COPD underdiagnosis and misdiagnosis in primary care and identify factors associated with COPD underdiagnosis in this setting. Methods COPD was defined as post-bronchodilator (post-BD) forced expiratory volume in 1 second/ forced vital capacity (FEV1/FVC) <0.70 and the lower limit of normal (LLN). Prior diagnosis was self-reported physician diagnosis of emphysema, chronic bronchitis, or COPD. Those patients with spirometric COPD were considered to have correct prior diagnosis, while those without spirometric criteria had misdiagnosis. Individuals with spirometric criteria without previous diagnosis were considered as underdiagnosed. Results 1,743 patients were interviewed, 1,540 completed spirometry, 309 (post-BD FEV1/FVC <0.70) and 226 (LLN) had COPD. Underdiagnosis using post-BD FEV1/FVC <0.70 was 77% and 73% by LLN. Overall, 102 patients had a prior COPD diagnosis, 71/102 patients 69.6%) had a prior correct diagnosis and 31/102 (30.4%) had a misdiagnosis defined by post-BD FEV1/FVC ≥0.70. Underdiagnosis was associated with higher body mass index (≥30 kg/m2), milder airway obstruction (GOLD I-II), black skin color, absence of dyspnea, wheezing, no history of exacerbations or hospitalizations in the past-year. Those not visiting a doctor in the last year or only visiting a GP had more risk of underdiagnosis. COPD underdiagnosis (65.8%) and misdiagnosis (26.4%) were less prevalent in those with previous spirometry. Conclusions COPD underdiagnosis is a major problem in primary care. Availability of spirometry should be a priority in this setting. © 2016 Casas Herrera et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.